Reviving the architectural heritage elements of the facades of new buildings in heritage areas - Raghda Abdel Ghader Mahmoud; Mohanad Ali Mohamed Fouda; Lamis Saad eldin El-Gezawi (JES: Journal of Engineering Sciences, 2020)
The research aims to monitor and analyze the architectural styles of new buildings located in heritage areas and to study the similarity and extent to which they are different from the architectural models prevailing in the heritage areas in terms of the elements and architectural vocabulary of the facades of buildings such as (shape - openings – decorations, etc.). Accordingly, this analytical study was carried out on a number of facades of new buildings, whose facades mimic the old architectural styles of heritage buildings in the cities of Sana'a, Yemen, Beirut, Lebanon, Muscat, Oman, and The cities of Alexandria and historic Cairo, Egypt, where the study is based on the analysis of the vocabulary of the facades of those New buildings are compared to the same vocabulary as the old façades of the original style.